A Commodity Price Index of Business Cycles - Persons, Warren M.; Coyle, Eunice S. (The Review of Economics and Statistics, 1921)
T HE object of this study is to construct an index of wholesale commodity prices for a special purpose. That purpose is to measure changes in general business conditions during alternating periods of prosperity and depression. In other words, our problem is to select and combine seriesof wholesale prices of commodities in order to secure an index of business cycles. This is not the problem which, heretofore, makers of commodity price index numbers have had before them; their problem has been, rather, to measure changes in the cost of living or in the general exchange value of money. The price index of business cycles, which we present here, is a new type of index number constructed by methods adapted to the special object in view.